A randomized controlled trial of the "positive diary" intervention for family caregivers of people with dementia. Issue 4 (23rd December 2021) - Fuju, Taiga; Yamagami, Tetsuya; Yamaguchi, Haruyasu; Yamazaki, Tsuneo
Abstract: Purpose: We examined the effectiveness of the "positive diary, " in which family caregivers of people with dementia write down three good things that happened with reasons at the end of each day. Design and Methods: In this randomized controlled trial, the intervention group used the "positive diary, " while the control group kept a record of each meal for 4 weeks. Findings: The intervention group showed improvement on several measures of wellbeing including Neuropsychiatric Inventory Questionnaire and Center for Epidemiologic Studies Depression Scale. Practice Implications: The "positive diary" is a useful self‐care tool for caregivers of people with dementia.